Prostrating in The Cloud: Faith, Identity, and the New Frontiers of Islamic Civilization - Reza Fahmi; Prima Aswirna (Journal of Psychology and Social Sciences, 2026)
Introduction: The digital transformation of religious life has propelled Islamic worship into immersive virtual environments, signaling a shift in the structural expression of Islamic civilization. This study explores the emergence of "virtual spirituality" and how the "civilizational center" of Islam is transitioning from physical mosques to a global digital ummah defined by networked connectivity. Methods: Using a qualitative framework grounded in social construction theory and media ecology, the research employed digital ethnography and phenomenological interviews with 20 Muslim participants to examine the reconstruction of sacredness within metaverse platforms. Results: Findings reveal that virtual worship facilitates a heightened sense of shared presence through avatar-mediated embodiment. This allows for synchronized ritual movements that mirror traditional congregational rhythms. The data suggests that in these environments, sacredness is no longer derived from material architecture but from collective intentionality and symbolic interaction. Discussion: The study introduces virtual spirituality as a hybrid mode of religiosity. While providing opportunities for transnational solidarity and pedagogical innovations like immersive Hajj simulations, it introduces risks such as the commodification of sacred spaces and the fragmentation of scholarly authority by algorithms. The research concludes that Islamic civilization requires renewed theological engagement and digital literacy to ensure technological advancements enhance, rather than diminish, spiritual depth.